Pengaruh Pendidikan Dan Pelatihan Terhadap Kinerja Kerja Pegawai Negeri Sipil (PNS) Pada Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Seram Bagian Barat - Semuel Souhoka (P3M Politeknik Negeri Ambon, 2024)
The aims of this research are 1). To determine the influence of education on the performance of civil servants at the West Seram Regency Population and Civil Registration Service Office. 2). To determine the effect of training on the performance of civil servants at the West Seram Regency Population and Civil Registration Service Office. 3). To determine the influence of education and training on the performance of civil servants at the West Seram Regency Population and Civil Registration Office. The analytical tools used are Classical Assumption Test, Descriptive Analysis, Multiple Linear Regression, Hypothesis Testing. The research results obtained that: 1). Education and training simultaneously have a significant effect on the performance of Civil Servants. 2). Education partially has a significant effect on the performance of Civil Servants. 3). Partial training has a significant effect on the performance of Civil Servants. 4). Variations in employee performance are explained by education and training by 79.6%, while 20.4% are explained by other variables not analyzed in the model, including work stress, work environment, etc. Keywords: Education, Training, Performance